“Monitoreo de la deforestación en las provincias de San Martín, picota y Bellavista en el departamento de San Martín-Perú” - Ozambela Dávila, Melita (2006)
This work presents the results of the study "Monitoring deforestation in the provinces of San Martín, Picota, and Bellavista in the department of San Martín". Its purpose was identify and quantify the increase in deforestation, using spatial indication of the changes in the forest cover with remote perception systems (teledetection) and geographic information systems, as well as to identify and describe the socio-economic processes that determine the progress of deforestation, in the influence area. For the monitoring 1 used Landsat TM5 and TM7 satellite images from 1986 and mosaic of images of ali the region of San Martín from 1999. These images were geometrically corrected and treated for their subsequent analysis. The analysis was optical or visual (digital format) directly from the scream using printed images as an aid characterizing units. For ground trusting realized rapid survey, registering various types of cover and land use satellite images. The results are presented in a mosaic of satellite images from 1986 and 1999, in maps of changes in vegetation cover and land use as well as deforestation for both years, and a map of the changes in deforestation over 13 years. 1 include charts, graphics and a matrix of changes that facilitate interpretation of results. 1 determine that the deforested surface over 13 years provinces were: Picota 22,219.64 has. (annual rate of 2.62 %), Bellavista 15,538.80 has. (annual rate of 0.28 %) and San Martín 9,552.07 has. (annual rate of 0.5%). These processes of deforestation are the ultimate effects of the disordered occupation of the territory.